Preliminary observations on the movement ecology of a crested horn shark (Heterodontus galeatus). Issue 2 (21st September 2021) - Bass, Nathan Charles; Day, Joanna; Guttridge, Tristan L.; Knott, Nathan A.; Brown, Culum
Abstract: The residency and movements of a single acoustically tagged female crested horn shark ( Heterodontus galeatus ) were monitored in Jervis Bay, Australia. The individual was intermittently detected by receivers throughout the 8‐year study period and showed preference for particular rocky reefs in terms of its residency indices and duration of residency events. This individual exhibited lower residency and dissimilar movement patterns to that of the well‐studied and sympatric Port Jackson shark ( Heterodontus portusjacksoni ), highlighting the need for research into the basic life history and movement ecology of H. galeatus .